STRATEGIES FOR INCREASING THE EFFICIENCY OF THE DENTAL PRACTICE ACTIVITY - PART I - Lupu Iulian Costin; Mihăilă Constantin Bogdan; Ovidiu Stamatin; Roxana Ionela Vasluianu; Doriana Agop-Forna; Tibeică Silviu Cătălin; Consuela Norina Forna (Romanian Dental Association for Education, 2023)
Legislative changes in the field, the consequences of the COVID-19 pandemic, cause dentists to look for strategies to make medical activity more efficient. The goal of these strategies is to achieve better quality treatments with a shorter allocated time within a "friendly" scheduling agenda based on quality communication with team members and patients. These strategies relate to different aspects of the office's organizational activity, with the aim of achieving an improvement in the dental services offered. The proposed strategies address the improvement of the work schedule, through an increased predictability of the time allocated to each type of dental procedure followed by the grouping of treatments in a therapy session of longer duration. The grouping of treatments, a better organized scheduling agenda, standardized protocols are some of the strategies that can bring efficiency and marked improvement in the activities of the dental office.